A TRAINING PROGRAM FOR THE CERTIFIED PUBLIC ACCOUNTANT'S STAFF. - Husband, George R. (The Accounting Review, 1947)
Abstract The article focuses on the usefulness of training programs for the public accountants staff. During the period of the world wars both the armed forces and industry made extensive use of special training programs to meet the challenge of new demands and to solve the problems created by the sudden loss of experienced employees. It was demonstrated that by the use of proper training methods individuals could be brought to the stage of respectable performance in relatively short periods of time. Millions of individuals were trained to meet the multiple demands of a modern army and millions of others with little or no experience in the mechanical arts were trained to take their places in industry. This was done with such efficiency that in a period little longer than that which it normally takes an individual to acquire a college degree an important part was played in defeating an experienced and seasoned enemy. While it is true that assistance was given by pressures and incentives that do not ordinarily exist in more normal civilian activities, accomplishments in many situations were little less than phenomenal.